Clinical Characteristics of Cognitive Impairment and 1-Year Outcome in Patients With Anti-LGI1 Antibody Encephalitis - Hang, Hai-lun; Zhang, Ji-hong; Chen, Dao-wen; Lu, Jie; Shi, Jing-ping (Frontiers in Neurology, 2020)
Introduction： Anti-leucine-rich glioma-inactivated 1 antibody (Anti-LGI1) encephalitis is the second most common autoimmune encephalitis. Anti-LGI1 encephalitis presented with acute to sub-acute onset of cognitive impairment，psychiatric disturbances, convulsions and faciobrachial dystonic seizures (FBDS)，hyponatremia. The common sequelae of Anti-LGI1 encephalitis is cognitive disorder, but there are few studies on the recovery of cognitive function after immunotherapy. This study was to explore clinical characteristics of cognitive impairment and one year outcome in patients with anti-LGI1 encephalitis. Methods: We retrospectively analyzed the clinical informationand cognitive impairment features of 21 patients admitted to the Nanjing Brain Hospital who had been diagnosed with anti-LGI1encephalitis from 2016 to 2019. At the time of onsetof hospitalizationand one year after discharge, the cognitive functions in these patients were assessed using two cognitive screening tools - Mini Mental State Examination (MMSE) and Montreal Cognitive Assessment-Basic (MoCA-B). Results: Among the 21 patients, 13 were males and 8 were females, aged 51.10±14.69（age range 20 to 72）years. Nineteen patients, comprising 90.48%, had recent memory deterioration. Routine EEG results of 13 cases were abnormal. EEG results were epileptic or slow waves activity involving the temporal lobes. Brain MRI results of 11 cases were abnormal, and the focus involved mediotemporal lobe and hippocampus. The decrease of short-term memory [recall scores：0.57±0.81(MMSE), 0.76±1.34(MoCA-B)] is the most obvious at the time of admission. After the combined treatment of IV methylprednisolone and immunoglobulins, the patient’s clinical symptoms improved obviously. Total MMSE and MoCA-Bscores of patients were significant increased after one year（21.19±3.54 vs.26.10±3.02, P<0.001）,（19.00±4.38 vs. 25.19±4.25, P<0.001）, respectively. Recall scores, orientation scores of MoCA-B were significant improved after one year（0.76±1.34 vs.3.24±1.48, P<0.001）（3.10±1.26vs.5.00±1.22, P<0.001）, respectively. However, 3/21(14.29%) patients still have obvious short-term memory impairment (Recall scores≤1). Conclusion: Cognitive impairment is one of the most common manifestations of anti-LGI1 encephalitis, with the main prominent being acute or subacute short-term memory loss.Although most patients with anti-LGI1encephalitis respond well to immunotherapy, a small number of patients still have cognitive disorders, mainly recent memory impairment, after one year.